Existence of Positive Solutions of Nonlinear Second-Order Periodic Boundary Value Problems. (25th November 2010) - Ma, Ruyun; Gao, Chenghua; Chen, Ruipeng
Abstract : This paper is devoted to study the existence of periodic solutions of the second-order equationx ′′ = f ( t, x ), wheref is a Carathéodory function, by combining a new expression of Green's function together with Dancer's global bifurcation theorem. Our main results are sharp and improve the main results by Torres (2003).